2018
DOI: 10.3389/fgene.2018.00117
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Gene Transfer and Gene Editing in Sterlet (Acipenser ruthenus)

Abstract: The sturgeon (Acipenseriformes) is an important farmed species because of its economical value. However, neither gene transfer nor gene editing techniques have been established in sturgeon for molecular breeding and gene functional study until now. In this study, we accomplished gene transfer and gene editing in sterlet (Acipenser ruthenus), which has the shortest sexual maturation period of sturgeons. The plasmid encoding enhanced green fluorescent protein (EGFP) was transferred into the embryos of sterlet at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 47 publications
2
22
0
1
Order By: Relevance
“…Our present study was aimed to disrupt the Ardnd1 to achieve sterility in sterlet ( Acipenser ruthenus ) to prepare a host for surrogate production in critically endangered sturgeon species. This study is consistent with Chen et al, [53], suggesting that Cas9 endonuclease can be efficiently applied in sturgeon having a higher ploidy level such as hexaploid or octoploid genomes.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our present study was aimed to disrupt the Ardnd1 to achieve sterility in sterlet ( Acipenser ruthenus ) to prepare a host for surrogate production in critically endangered sturgeon species. This study is consistent with Chen et al, [53], suggesting that Cas9 endonuclease can be efficiently applied in sturgeon having a higher ploidy level such as hexaploid or octoploid genomes.…”
Section: Discussionsupporting
confidence: 93%
“…In fish model species, zebrafish, the CRISPR/Cas9 research with codon optimization of Cas9 mRNA showed induction of mutation with 75 to 99% rates in endogenous genes [52]. However, same method does not induce more than 55% mutation in sterlet, which might be due to different characteristics of embryos such as size, incubation temperature, cleavage pattern and ploidy level [53]. Interestingly, in sterlet when Cas9 protein instead of Cas9 mRNA was injected, mutation and survival rate of embryos increased by more than 90% [53].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Atlantic salmon dnd, tyr, slc24a5 (C) [60,61] Sturgeon dnd (C) [62] Atlantic killifish ahr2 (C) [63] Tilapia fox12a, c yp19a1 a, dmrt1, nanos, gsdf, sf-1/nr5a, mstn (C); rspo1, fox12a, c yp19a1 a (T) [64][65][66][67][68][69] Cavefish oca2 (T) [70] Channel catfish lh (Z) [71] Chinese lamprey slc24a5 (C) [ Medaka dnd (M); fox13, dmy, dmc1, fshb, gnrh1 (T); gsdf (Z) [110][111][112][113][114] Red sea bream mstn (C) [115] Rice field eel dmrt1, foxl2, cyp19ala (T) [116] Rohu tlr22 (C) [117] Starlet and sturgeon Ntl, dnd (T & C) [118,119] M, morpholino; Z, zinc finger nuclease (ZFN); T, transcription activator-like effector nucleases (TALEN), C, clustered regularly interspaced short palindromic repeats (CRISPR).…”
Section: Fishesmentioning
confidence: 99%
“…自此, 基因组编辑在多种养殖鱼类中得到了应用, 如虹 鳟 [151] 、罗非鱼 [152] 、鲤 [153] 、大西洋鲑 [154] 、斑点叉尾 鮰 [155] 、黄鳝 [156] 、半滑舌鳎 [157] 和小体鲟 [158] 等. 基因 组编辑技术将在水产养殖动物基因功能解析和经济性 状精准设计育种中发挥重要作用 [102,145,149] .…”
Section: 基于全基因组信息及分子设计等前沿育种 技术unclassified